Complications of Glaucoma Drainage Device Surgery: A Review. (November 2014) - Giovingo, Michael
Abstract Purpose: To review current literature on the complications of the use of glaucoma drainage device surgery. Summary: The use of glaucoma drainage devices has increased significantly in recent years for both primary treatment of glaucoma and refractory glaucoma. The efficacy and safety of glaucoma drainage devices has been well established, so they are a viable surgical option in patients who fail medical therapy. With the increased use of these devices, understanding their complications is essential in managing these patients. The prevention and management of complications associated with glaucoma drainage device insertion has some similarities to that of a trabeculectomy. The glaucoma drainage devices have additional complications associated with the fact that hardware is left within the eye. There have been no definitive answers as to the perfect surgical technique to prevent complications but careful surgical performance, tube placement and use of a double-layered graft over the tube are likely to lead to a better outcome. The rate of complications also dictates careful follow up to identify these complications early in their process as early intervention will likely lead to better outcomes.